6(7+3n)-7(-8n+1)=-39

Simple and best practice solution for 6(7+3n)-7(-8n+1)=-39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(7+3n)-7(-8n+1)=-39 equation:


6(7+3n)-7(-8n+1)=-39

We simplify the equation to the form, which is simple to understand
6(7+3n)-7(-8n+1)=-39

Reorder the terms in parentheses
+(+42+18n)-7*(-8n+1)=-39

Remove unnecessary parentheses
+42+18n-7+*(-8n+1+)=-39

Reorder the terms in parentheses
+42+18n+(+56n-7)=-39

Remove unnecessary parentheses
+42+18n+56n-7=-39

We move all terms containing n to the left and all other terms to the right.
+18n+56n=-39-42+7

We simplify left and right side of the equation.
+74n=-74

We divide both sides of the equation by 74 to get n.
n=-1

See similar equations:

| 3858.25=1925+175.75x | | x-0.15x-9.00=42.00 | | 4x^2=20x-5x^2 | | 5-a/a=3/4=7/a | | -1/3x2/-5 | | 4+3p-2=9p+9-5p | | r+4r-9=4r-5 | | -7(2x-9)=-14x-63 | | 1178.00=175.00+343.00+16.50x | | 6x+24=2x+52 | | x-0.25x-8.00=22.00 | | -4w-16=-4(w+4) | | -3u+6=-21 | | 3(x+-7)+5=26 | | 3(x-3)=6x+45 | | 1+8(x-7)=7-7(x-4) | | 2=-2/v | | (a+i)(4-bi)=3b+2ai | | b/5=7/6 | | 8v+36=-7v | | 4-2(5b-1)=86 | | 5(-5-7p)=7-3p | | -3u+6=21 | | 8y+-10=-3y+2 | | 150x+310=350 | | -x(x)-3x+10=6 | | .5(12x-4)-(x+5)= | | w(3-2w)=14 | | 864.50=185.00+267.00+16.50x | | 5x-(4x+2)=6 | | w(2-2w)=14 | | 3x-12=52-5x |

Equations solver categories